Sistem Pendidikan di Negara Singapura - Fika Aulia Putri; Jefriman Akmal; Mislaini Mislaini (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
The education system in Singapore is known for its effective teaching methods and high academic results in international tests. This makes education in Singapore can be said to be advanced. The education system in Singapore has evolved from the traditional British education model to be more adaptive and innovative, with a focus on individual and talent development. Singapore is also implementing various educational reforms to increase global competitiveness, such as "Thinking Schools, Learning Nation" which encourages critical thinking skills. This research aims to analyze the education system in Singapore as a comparison with Indonesia. The research method used is library research where data sources are obtained from books, articles, journals and other reading materials. This research can produce knowledge about the education system in Singapore and comparisons with Indonesia.